Approach for reduced test suite generation based on predicate abstraction - Xi GUO; Huan-guo ZHANG (Tongxin xuebao, 2012)
Aim to the problem of status space explosion due to the growing number of status transition of large scale software system,a reduced test suite generation approach based on predicate abstraction was proposed,which divided the status space of the software model according to the gi predicates to get the equivalence classes.The reduced abstract status was settled using the mapping between the status sets,and generated the reduced test suite based on the transition of the status.The results of experiments indicate tha this approach can reduce the status of the model efficiently,and generate smaller size of test suite.